2000
DOI: 10.1038/sj.jea.7500123
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of selected pesticide metabolites in human urine using isotope dilution high-performance liquid chromatography/tandem mass spectrometry

Abstract: The annual domestic use of pesticides is continually increasing, virtually ensuring that everyone is exposed to some level of pesticides on a regular basis through diet or environment. The potential developmental and physical adverse effects these chronic pesticide exposures have on children are of increasing concern. To adequately evaluate the potential adverse effects resulting from these exposures, accurate methods to measure the amount of the pesticide absorbed by the body must be developed. We have develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 18 publications
3
36
2
1
Order By: Relevance
“…Detection limits, precision, and analytical recovery were similar to urine methods (Baker et al 2000;Barr et al 1999;Beeson et al 1999;Bravo et al 2002;Shealy et al 1996). Metabolites derived from naphthalene, carbaryl, para-dichlorobenzene, ortho-phenylphenol, carbofuran, pentachlorophenol, and OP pesticides were detected in this small sample of amniotic fluid samples, indicating that fetal exposures to these compounds occur as early as 15-18 weeks gestation, possibly during sensitive developmental periods.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Detection limits, precision, and analytical recovery were similar to urine methods (Baker et al 2000;Barr et al 1999;Beeson et al 1999;Bravo et al 2002;Shealy et al 1996). Metabolites derived from naphthalene, carbaryl, para-dichlorobenzene, ortho-phenylphenol, carbofuran, pentachlorophenol, and OP pesticides were detected in this small sample of amniotic fluid samples, indicating that fetal exposures to these compounds occur as early as 15-18 weeks gestation, possibly during sensitive developmental periods.…”
Section: Discussionmentioning
confidence: 69%
“…Laboratory methods involved a solid-phase or liquid partitioning extraction with analysis using tandem mass spectrometry and isotope dilution gas chromatography-mass spectrometry/mass spectrometry methods previously developed by the CDC for urine. Detailed descriptions of these analytical procedures are presented elsewhere (Baker et al 2000;Barr et al 1999;Beeson et al 1999;Bravo et al 2002;Shealy et al 1996;Whyatt and Barr 2001). Because amniotic fluid is similar to urine, no major modifications in methodology were required, although minor changes were necessary (described in "Results").…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies carried out in the European Union and the United States have shown detectable amounts of pyrethroid metabolites in urine samples from the general population (Schettgen et al, 2002;Baker et al, 2000). No evidence of adverse effects has been reported for such levels of exposure.…”
Section: Effects On Humansmentioning
confidence: 99%
“…(58) razvili su metodu tekućinske kromatografi je povezane s tandemnom spektrometrijom masa (LC-MS/MS) uz kemijsku ionizaciju analita pri atmosferskom tlaku za određivanje atrazin merkapturata u urinu. Modifi kacija te metode primijenjena je za određivanje razina atrazin merkapturata u urinu ispitanika iz opće populacije (54). LC-MS/MS uz kemijsku ionizaciju pri atmosferskom tlaku primijenjena je za određivanje 18 specifičnih biomarkera najčešće upotrebljavanih pesticida (56) i za određivanje razina izvornih spojeva i njihovih metabolita u urinu poljoprivrednih radnika (57).…”
Section: Slika 1 Prikaz Metaboličke Razgradnje Atrazina Kod Glodavacaunclassified